EFEKTIVITAS TEKNIK MIND MAPPING TERHADAP KEMAMPUAN HIGHER ORDER THINKING SKILL PADA SISWA KELAS VIII SMP - Azam, Ismul; Astuti, Farida Herna; Jaswandi, Lalu (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
ABSTRACT Higher Order Thinking Skill (HOTS) can be understood as a higher-level thinking ability that involves critical, logical, and creative thinking processes. This ability is reflected in cognitive activities such as analyzing, evaluating, and creating. The problem underlying this research is the still low level of higher-order thinking skills among students, which may affect their readiness to face various learning challenges in the 21st century. This study aims to analyze the effectiveness of applying the mind mapping technique in improving students’ Higher Order Thinking Skills. This research employed a quantitative approach with a quasi-experimental design in the form of a nonequivalent control group design. The population of this study consisted of 239 eighth-grade students at SMP Negeri 8 Mataram in the 2022/2023 academic year. The sample in this study consisted of 68 students, including 34 students in the experimental class and 34 students in the control class. The sample was determined using the simple random sampling technique. Data collection in this study used questionnaires as the main method, while observation, interviews, and documentation were used as supporting methods. Data analysis was conducted using the t-test to identify differences in HOTS abilities between the two groups. The results of the data analysis showed that the calculated tvalue (tcount) of 6.485 was greater than the ttable value at the 5% significance level, which was 2.262 (6.485 > 2.262). Therefore, H₀ was rejected and Hₐ was accepted. Based on these findings, it can be concluded that the application of the mind mapping technique is proven to be effective in significantly improving the Higher Order Thinking Skills of eighth-grade students at SMP Negeri 8 Mataram in the 2022/2023 academic year. ABSTRAK Higher Order Thinking Skill (HOTS) dapat dipahami sebagai kemampuan berpikir tingkat tinggi yang mencakup proses berpikir kritis, logis, serta kreatif. Kemampuan ini tercermin melalui aktivitas kognitif seperti menganalisis, mengevaluasi, dan menciptakan. Permasalahan yang melatarbelakangi penelitian ini adalah masih rendahnya kemampuan berpikir tingkat tinggi pada siswa, yang berpotensi memengaruhi tingkat kesiapan mereka dalam menghadapi berbagai tantangan pembelajaran di abad ke-21. Penelitian ini bertujuan untuk menganalisis efektivitas penerapan teknik mind mapping dalam meningkatkan kemampuan Higher Order Thinking Skill pada siswa. Penelitian ini menggunakan pendekatan kuantitatif dengan rancangan quasi experiment berupa nonequivalent control group design. Jumlah populasi dalam penelitian ini adalah 239 siswa kelas VIII di SMP Negeri 8 Mataram pada Tahun Pelajaran 2022/2023. Jumlah sampel dalam penelitian ini adalah 68 siswa, yang terdiri atas 34 siswa pada kelas eksperimen dan 34 siswa pada kelas kontrol. Penentuan sampel dilakukan dengan menggunakan teknik simple random sampling. Pengumpulan data dalam penelitian ini menggunakan angket sebagai metode utama, sedangkan observasi, wawancara, dan dokumentasi dimanfaatkan sebagai metode pendukung. Analisis data dilakukan dengan menggunakan uji t-test untuk mengidentifikasi perbedaan kemampuan HOTS antara kedua kelompok. Hasil analisis data menunjukkan bahwa nilai thitung sebesar 6,485 lebih besar dari nilai nilai ttabel pada taraf signifikansi 5% yaitu 2,262 (6,485 > 2,262), sehingga H₀ ditolak dan Hₐ diterima. Berdasarkan hasil penelitian tersebut, dapat disimpulkan bahwa penerapan teknik mind mapping terbukti efektif dalam meningkatkan kemampuan Higher Order Thinking Skill siswa kelas VIII di SMP Negeri 8 Mataram Tahun Pelajaran 2022/2023 secara signifikan.